Why Religious Freedom Matters for Democracy: Comparative Reflections from Britain and France for a Democratic Vivre Ensemble - Hunter-Henin, Myriam (Hart Studies in Comparative Public Law Ser., 2020)
Intro -- Acknowledgements -- Table of Contents -- Table of Cases -- Table of Statutory Materials -- 1. Introduction -- I. Goals of the Book -- II. Summary of my Main Argument -- III. Structure of the Argument -- IV. Conclusion -- PART I: THE BROKEN VIVRE ENSEMBLE - OBSERVATIONS AND SOLUTIONS -- 2. Contextual Analyses: Laïcité and the Democratic Vivre Ensemble -- I. The Historical Layers of Laïcité: From Hostility to Tolerance towards Religion -- II. Laïcité, Common Values and Islam -- III. Conclusion to Chapter 2 -- 3. Contextual Analyses: The English Experience of Vivre Ensemble -- I. Church Establishment: an Inclusive Type of Secularism? -- II. British Values, Religious Autonomy and Liberalism -- III. Conclusion to Chapter 3 -- 4. Conceptual Framework: The Liberal Democratic Vivre Ensemble -- I. Why Religious Freedom Matters for Democracy -- II. Why Pluralism Matters for Democracy and Religious Freedom -- III. Conclusion to Chapter 4 -- PART II: CASE STUDIES: THE MENDED VIVRE ENSEMBLE -- 5. Lessons from Achbita -- I. Spheres over Principles -- II. Consistency over Proportionality -- III. Conclusion to Chapter 5 -- 6. Beyond Achbita: Possible Ways Forward -- I. Laïcite: Deference rather than Delegation -- II. Proportionality rather than Autonomy -- III. Religious Freedom and Equality Rights -- IV. Conclusion to Chapter 6 -- V. Conclusion of Part II -- 7. Conclusion -- I. For a Democratic Approach to Religious Freedom -- II. Consequences of the Democratic Approach for the Courts -- Appendix -- Index.